ANOVA-based performance evaluation of hybrid fibre-reinforced ECC with quarry dust in structural repair applications - Mareena George; Dhanya Sathyan (Materials Research Express)
Engineered cementitious composites (ECC) are high-performance materials known for their exceptional ductility and micro-cracking behaviour due to the inclusion of small percentages of synthetic fibres. This characteristic makes ECC a promising alternative to conventional concrete. However, the high cost of silica sand, a key component of ECC, and the limited availability of polyvinyl alcohol fibres hinder its widespread adoption. Quarry dust powder (QDP), a byproduct of the manufactured sand production process, presents a significant environmental challenge due to its disposal. This study focuses on checking the suitability of quarry dust powder in replacing the silica sand of ECC. Quarry dust powder with particle size <150 μm is added by 5,10,15% by the total weight of the mix and its statistical significance is analysed using ANOVA. Also, the hybridization of fibre is done using 50% Polyvinyl Alcohol fibre (PVA)- 50% Polypropylene fibre (PP) combination and 50% PVA -50% Steel fibre (ST) combination of the total fibre content. The water binder ratio is varied by 0.35,0.32, 0.30.0.28. The acceptability of the ECC is checked by comparing its density, compressive strength, flexural strength, uniaxial tension test and sorptivity test. The repair property of the mix is analysed using bond strength tests like the splitting prism test and slant shear test. The pozzolanic activity of quarry dust powder is analysed using the strength activity index. An optimum mix is determined according to the findings as 10% of the total mix as quarry dust powder, 50% PVA-50%PP combination of total fibre and 0.3 water binder ratio. A surface plot is created using response surface plot to get a graphical representation of all parameters. Interaction plots and main effects plots are used as tools for visualizing and understanding the effects of dependent and independent variables. ANOVA models are developed for each parameter for future research in this area.